Socialization of Bilingual Method Integration in Teaching at Meilia Medika Vocational School" : Sosialisasi Integrasi Metode Bilingual dalam Pembelajaran Di SMK Meilia Medika - Ulfa, Rima Novia; Octavita, Rr. Astri Indriana; Yuliana, Tiarma Ika; Ghufron, M. Ali (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
The purpose of this community service activity is to provide socialization about the integration of bilingual methods. The mastery of foreign languages is something that cannot be dismissed in the current era of globalization. Therefore, the Unindra abdimas team conducted a socialization to integrate bilingual learning methods (Indonesian and English) in learning at SMK Meilia Medika. This activity was carried out to improve students' competence in English and prepare them to face competition in the global workforce. Activities carried out in the form of intensive training for teachers, preparation of bilingual teaching materials, and implementation of bilingual classes in several subjects. Through this socialization, it is hoped that all stakeholders, including teachers, students, and parents, will understand the importance of the bilingual method and play an active role in its success. The expected outcome of this program is the improvement of students' English language skills and the creation of a more dynamic and interactive learning environment.